2010
DOI: 10.1118/1.3455705
|View full text |Cite
|
Sign up to set email alerts
|

Variability in PET quantitation within a multicenter consortium

Abstract: Purpose: The purpose of this study was to evaluate the variability in quantitation of positron emission tomography ͑PET͒ data acquired within the context of a multicenter consortium. Methods: PET quantitation phantoms designed by American Association of Physicists in Medicine/ Society of Nuclear Medicine Task Group 145 were sent to the ten member sites of the Pediatric Brain Tumor Consortium ͑PBTC͒, a NIH-funded research consortium investigating the biology and therapies for brain tumors in children. The phant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
101
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 17 publications
0
101
0
Order By: Relevance
“…Many of these additional sources of error are reviewed elsewhere. 4,5,39,40 Finally, we note that the increased instrumentation variability found in multicenter calibration studies 37,38 compared to the results presented here imply that multicenter patient test-retest variances can be much higher than for single-site studies, as was recently demonstrated in the study by Velasquez et al 25 The observed biases between the RC curves from the three scanners is a likely major contributor to the reported larger variances for multicenter imaging of the same phantom. 37,38 A limitation of this study, and the multicenter and patient test-retest studies discussed above, is that there is no evaluation of the long-term variability of scanner calibration.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Many of these additional sources of error are reviewed elsewhere. 4,5,39,40 Finally, we note that the increased instrumentation variability found in multicenter calibration studies 37,38 compared to the results presented here imply that multicenter patient test-retest variances can be much higher than for single-site studies, as was recently demonstrated in the study by Velasquez et al 25 The observed biases between the RC curves from the three scanners is a likely major contributor to the reported larger variances for multicenter imaging of the same phantom. 37,38 A limitation of this study, and the multicenter and patient test-retest studies discussed above, is that there is no evaluation of the long-term variability of scanner calibration.…”
Section: Discussionmentioning
confidence: 49%
“…2 of Boellaard et al 13 and Kinahan et al 37 use the same phantom design as used here although in the Boellaard study the phantom was filled with aqueous F-18. In addition, the more recent study by Fahey et al 38 used a compromise approach with a different ACR phantom by adding Ge-68 to the hot targets and F-18 to the background. All three of those studies, however, used single measurements at multiple sites and thus the variances reported were due a combination of bias and variance from each site.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 10.5% decrease was computed retrospectively to obtain the statistically best split. Current clinical PET systems may not have the reproducibility to reliably detect a change of 10.5% (15). The 10.5% threshold will need to be prospectively confirmed as an appropriate cutoff for this form of therapy in this type of tumor.…”
Section: Day-9 Pet Predicts Os In Ewing Sarcoma • O Et Almentioning
confidence: 99%
“…Incr easingly, 18 F-FDG and other radiopharmaceuticals are being used as PET/CT quantitative imaging biomarkers in oncology to assess treatment efficacy (1)(2)(3)(4)(5)(6)(7)(8). Although many factors, both physiologic and instrumental (9)(10)(11)(12), influence quantitative accuracy, the ability to determine treatment efficacy on the basis of PET is predicated on the ability of PET scanners to provide stable measurements of radiotracer concentrations-thus allowing the treatment response to be tracked over months or years.…”
mentioning
confidence: 99%
“…It has been reported that approximately one-third of PET studies acquired at community-based imaging facilities may lack the necessary information to obtain quantitative imaging data (17). In addition, quantitative variability in multicenter trials can be expected to be larger than that in single-center trials (18,19). In a study at a single institution with multiple PET scanners, which were clinically accredited and maintained in accordance with manufacturer standards by qualified staff, the variance of PET measurements was shown to be greater in clinical practice than under ideal study settings (20).…”
mentioning
confidence: 99%